Partial budget analysis of prepartum antimicrobial therapy and Escherichia coli J5 vaccination of dairy heifers and their effect on milk production and milk quality parameters - Vargas,Renison T. (2016)
Abstract: This study aimed to determine whether prepartum antimicrobial and/or Escherichia coli J5 vaccination in dairy heifers influence the milk production, milk quality, and estimate their economic benefit. Thus, 33 dairy heifers were enrolled in four groups using a split-splot design. Groups were: (G1) prepartum antimicrobial infusion and vaccination with an E. coli J5 bacterin, (G2) prepartum antimicrobial infusion, (G3) vaccination with an E. coli J5 bacterin, and (G4) control heifers. Composite milk samples for somatic cell count, total bacteria count and milk composition were collected 15 days after calving and every 15 days until the end of the experiment. Bacteriological analysis was carried out at the end of study. The milk production and the incidence of clinical cases of mastitis, as well as the costs associated with them were recorded. The results demonstrate a reduction on clinical mastitis rates by preventive strategies, which implicated in lower volume of discarded milk (0.99, 1.01, 1.04 and 3.98% for G1, G2, G3 and G4, respectively) and higher economic benefit. Thus, in well-managed dairy herds the prevention of heifer mastitis by vaccination or antimicrobial therapy can reduce the amount of antimicrobials needed to treat clinical mastitis cases and the days of discarded milk.